Building A Restorative Property Justice Paradigm for Marital Assets in Indonesian International Marriages - Raden Maestro Broto Ariyo; FX Joko Priyono; Yunanto Yunanto; Herni Widanarti (Law Development Journal, 2026)
Indonesia’s mixed marriages expose a structural friction between the Marriage Law’s default of community property and the agrarian lex situs that bars foreign nationals from holding Hak Milik. This article proposes Restorative Property Justice (RPJ), a compliance first paradigm that aligns restorative values with land administration realities. Using a desk-based design (normative doctrinal analysis; PRISMA guided mapping of Indonesian decisions, 2015–2025; regulatory design review; and functional comparison to EU Reg. 2016/1103), researcher show that sustainable settlements pivot on registrability: mediation under PERMA 1/2016 must mature into a consent judgment, translate into the correct notarial/PPAT deed, and clear BPN’s documentary gates (PP 18/2021). Findings include a typology of disputes (A–C), evidence that value splitting and lawful conversion outperform title splitting, and a Court Notary/PPAT BPN decision flow that reduces execution risk. Researcher offer a clause toolkit (ring fencing, compensation+escrow, situs safe choice of law, third party protection, compliance covenants) and policy proposals to standardize mediation minutes/templates and align PPAT/BPN SOPs. RPJ reframes equity and legality as design variables, yielding settlements that are fair, portable, and executable.